Learning to see value-adding and non-value-adding work time in renovation production systems. Issue 8 (11th June 2022) - Neve, Hasse; Wandahl, Søren; Lindhard, Søren; Teizer, Jochen; Lerche, Jon
Abstract: For decades construction labour productivity has been stagnated or declining. Changing this issue requires new knowledge on the labour-intensive construction production system. The work sampling method was applied to collect data from three renovation construction production systems. It quantifies observations of on-site work and enables deep analyses of how time is used. The analysis revealed that the renovation projects had a baseline of value-adding-work (VAW) time on 29.5%. It further identified five system behaviours outlining how VAW and Non-Value-Adding work (NVAW) time behaves. The new knowledge of how both VAW and NVAW time behaves advances knowledge on how time is wasted in construction projects and opens new branches of future research. The findings are furthermore of potential use to industry professionals who work with process improvement in renovation projects because they provide, among others, answers to how targets can be defined for both VAW and NVAW.